Pengaruh dan Dampak Intervensi Orang Tua Terhadap Rumah Tangga Anak Perspektif Hukum Islam di Desa Mayang Jember - Wahdatur Rike Uyunul Mukarromah (Rechtenstudent, 2020)
There have been many cases containing the intervention or intervention of parents in the life of the child's family, along with the impacts that occur in the child's household. Having a family Ideally has your residence, not living with your parents (in-laws). With separate living quarters so that we can manage our household wheels. The authors also encountered a variety of Parental Interference Problems and their Impact on Children's Households. This is what makes the author interested in researching three families in Mayang Village, Mayang Subdistrict, Jember Regency who still live under the same roof as their parents who experience disharmony due to parents who should not have to interfere with their child's household.